Using passive control by a pendulum in a portal frame platform with piezoelectric energy harvesting - Rocha, Rodrigo T.; Balthazar, Jose M. [UNESP]; Tusset, Angelo M.; Piccirillo, Vinicius (Sage Publications Ltd, 2018)
This work presents a passive control strategy using a pendulum on a simple portal frame structure, with two-to-one internal resonance, with a piezoelectric material coupling as a means of energy harvesting. In addition, the system is externally base-excited by an electro-dynamical shaker with harmonic output. Due to internal resonance the system may present the phenomenon of saturation, which provides some nonlinear dynamical behavior to the system. A pendulum is coupled to control nonlinear behaviors, leading to a periodic orbit, which is necessary to maintain energy harvesting. The results show that the system presents, most of the time, as being quasiperiodic. However, it does not present as being chaotic. With the pendulum, it was possible to control most of these quasiperiodic behaviors, leading to a periodic orbit. Moreover, it is possible to eliminate the need for an active or semi-active control, which are usually more complex. In addition, the control provides a way to detune the energy captured to the desired operating frequency.
Keywords: Passive control; saturation phenomenon; energy harvesting; internal resonance; electro-dynamical shaker